Staff management and fingerprint login module of shop management system - Foong, Jek (2010)
Some of the small clothing stores or boutique shops are using different system to running different business activities such as cashier machine to handle business transaction, manually record stock information and staff personal detail or even not recording the information at all. For security and authentication level, this system used fingerprint authentication system to login to system. Fingerprints or thumb prints are the oldest and the most commonly known biometric and users can never change their unique identifier. Shop Management System will allow staff to take their attendance with using thumb print. Thumb print sign-in system will collect Staff attendance and calculate how many staffs are attended in the day. Besides, this system can check who were absent or late. Thumb Print system also more simply and secure it is because biometrics cannot be duplicated or hacked. It is also not necessary to remember unique user ID and password to gain entry to login into the system.